1992
DOI: 10.1039/p29920000213
|View full text |Cite
|
Sign up to set email alerts
|

Studies on biologically active acylhydrazones. Part 1. Acid–base equilibria and acid hydrolysis of pyridoxal aroylhydrazones and related compounds

Abstract: A series of pyridoxal aroylhydrazones has been synthesized and their UV, IF? and 'H NMR spectra studied. In neutral methanol these hydrazones exist in the enolimine form, while in aqueous solution (pH ca 7.0) they exist predominantly in the zwitterionic form in which the phenolic proton is transferred to the pyridine nitrogen. Their aqueous acid-base equilibria show three successive steps for which protonation constants have been determined. The different acidity constants are correlated with Hammett substitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The assignment of pK a values of ionisable protons in the HPCIH analogues conforms to reports of similar aroylhydrazones. [30][31][32][33][34][35][36] The first protonation constant (pK 1 ) is associated with the hydrazone N-NH-C=O group, while the lower pK a value (pK 2 ) is assigned to protonation of the 2-pyridyl ring, which is supported by crystallographic evidence reported here (Fig. 4).…”
Section: Protonation Constantssupporting
confidence: 78%
“…The assignment of pK a values of ionisable protons in the HPCIH analogues conforms to reports of similar aroylhydrazones. [30][31][32][33][34][35][36] The first protonation constant (pK 1 ) is associated with the hydrazone N-NH-C=O group, while the lower pK a value (pK 2 ) is assigned to protonation of the 2-pyridyl ring, which is supported by crystallographic evidence reported here (Fig. 4).…”
Section: Protonation Constantssupporting
confidence: 78%
“…2 In addition, for compounds of the 100 series, the calculations of log P calc values are uncertain because in neutral water solution the compounds do not have the structure 1 but the zwitterionic structure ( Fig. 3) (Lees-Gayed et al 1992;Richardson et al 1990). The zwitterionic form would be expected to be more soluble in water, and to have log P lower by an uncertain amount.…”
Section: Pitfalls In Calculations Of Log P By Rekker's Additive Methodsmentioning
confidence: 99%
“…So far, only one study reported rapid disappearance of CDX in various waters ( t 1/2 = 0.8−3.4 min) dosed with 1.0 mg Cl 2 /L of free chlorine, in which neither the effect of pH on reaction kinetics nor product formation were assessed (). CDX and DCDX are comprised of functional groups including N -oxide, hydrazone, and carbazate moieties that can be found in a broad range of pharmaceuticals, agrochemicals, and industrial chemicals for N -oxides ( , ), in medical agents and agricultural pesticides for hydrazones ( , ), and in weed-killing and fungicidal pesticides for carbazates ( , ). A fundamental understanding of the reactivity of these functional groups toward aqueous chlorine can have widespread applications.…”
Section: Introductionmentioning
confidence: 99%